ANALYSIS OF SELECTED ANTHROPOMETRIC VARIABLES AMONG UNIVERSITY BASKETBALL ANDHANDBALL PLAYERS - Singh, Harnek; Kumar, Dr. Ashok; Puri, Mehul (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The performance of players in various sports may be influenced by the anthropometric, physical and the physiological characteristics and may also aid in determining a suitable physique required for a sport. The physical variables such as Biceps and Triceps have been selected to assess the physical condition of the basketball players and handball players of different universities of Punjab. Data was collected from total 50 players and selected 25 each from both the basketball and handball players of Punjab. The results revealed that there is insignificant difference found in both the selected anthropometrical variables i.e Biceps and Triceps between the basketball and handball players of Punjab region